2012
DOI: 10.1080/10962247.2012.701193
|View full text |Cite
|
Sign up to set email alerts
|

Winter and Summer PM2.5 Chemical Compositions in Fourteen Chinese Cities

Abstract: PM 2.5 in 14 of China's large cities achieves high concentrations in both winter and summer with averages >100 g m À3 being common occurrences. A grand average of 115 g m À3 was found for all cities, with a minimum of 27 g m À3 measured at Qingdao during summer and a maximum of 356 g m À3 at Xi'an during winter. Both primary and secondary PM 2.5 are important contributors at all of the cities and during both winter and summer. While ammonium sulfate is a large contributor during both seasons, ammonium nitrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
184
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(199 citation statements)
references
References 95 publications
12
184
3
Order By: Relevance
“…Unlikely, Cao et al (2012) found high level of PM 2.5 in winter compared to summer in other regions in China. This is because the Northwest wind is the prevailing wind in spring and winter with a larger wind-speed in Bohai Sea.…”
Section: Concentration Of Pm 25 and Chemical Compositions At Tuoji Imentioning
confidence: 59%
“…Unlikely, Cao et al (2012) found high level of PM 2.5 in winter compared to summer in other regions in China. This is because the Northwest wind is the prevailing wind in spring and winter with a larger wind-speed in Bohai Sea.…”
Section: Concentration Of Pm 25 and Chemical Compositions At Tuoji Imentioning
confidence: 59%
“…On average, the most abundant water soluble species in PM 2.5 were ranked as follows: The concentration of ss-sulfate (sea salt sulfate) comprised b 5% of the total sulfate measured, suggesting that sulfate is mainly derived from anthropogenic activities and secondary formation. The average concentrations of SO 4 2− in Foshan are comparable with those in Chongqing city, and higher than representative megacities such as Beijing, Guangzhou and Shanghai (Yang et al, 2011b); and lower than the coal-smoke-polluted cities in Western China such as Xi'an (Cao et al, 2012 There is an increasing trend of nitrate/sulfate ratio, suggesting that the contribution of mobile emissions in Foshan is significantly increasing. However, in general the ratio was b1, implying that coal combustion is still a primary source.…”
Section: Temporal Variation Of Water Soluble Speciesmentioning
confidence: 76%
“…Beijing (Yang et al, 2011b) Chongqing (Yang et al, 2011b) Shanghai (Yang et al, 2011b) Guangzhou (Yang et al, 2011b) Chengdu (Tao et al, 2013) Xi'an (Cao et al, 2012) is an important manufacturing base in China, with coal as the primary energy source (Shen and Wei, 2012), and the production of ceramics in Foshan city contributes about 30% to total world production. Therefore, the restriction of coal combustion and the relocation of the ceramic industry from 2007 to 2010 dramatically reduced the emissions of elements from anthropogenic sources.…”
Section: Temporal Trend Of Inorganic Elementsmentioning
confidence: 99%
“…On the other hand, higher concentration of nitrate would relate with the artifact of HNO 3 from the evaporation of nitrate ammonium under the high temperature. Many earlier studies have also observed higher inorganic species concentrations in summer at Xi'an and Beijing (Duan et al, 2006;Cao et al, 2012;Hu et al, 2014). The high loadings of OC, EC and chloride in winter are likely related with vehicles, combustion emissions and the low temperature.…”
Section: Monthly Variations Of Chemical Components In Pm 25mentioning
confidence: 90%
“…A number of studies have dedicated to the characterization of particulate matter in recent years based on filters measurement and analysis in Beijing (He et al, 2001;Dan et al, 2004;Sun et al, 2004;Wang et al, 2005;Duan et al, 2006;Wu and Wang, 2007;Zhang et al, 2007;Pathak et al, 2009;Cao et al, 2012;Wang et al, 2013;Hu et al, 2014). These studies reported a lot of valuable results on PM and chemical composition in different years which make us understand aerosols properties better, but most of them focus on the characterization of aerosol at short-term measurements representing one or two seasons.…”
Section: Introductionmentioning
confidence: 99%